A Beacon of Hope to Women in Margaret Atwood’s the Testaments - Divya John, S. (International Journal of Recent Advances in Multidisciplinary Topics, 2021)
Women subjugation, religion, power are all the tools in the hands of the authority to keep their society under their control. Gileadean authorities don’t even allow their people to think of their selves and insists to act upon the wishes of the society only. They also use religion to fortify their plugs. In this article I would like to describe how cruel the Gileadean authority was to their people to maintain their power and the realization of some people about the injustices they are facing which result in the collapse of the kingdom. Men are not the enemies and the religion is not an evil but the society which makes twists and turns in their teaching makes so.